Restoring Fire-Grazer Interactions to Pursue Heterogeneity in Sandhills Prairie - Arterburn, Jack R.; Twidwell, Dirac; Wonkka, Carissa L.; Schacht, Walter H.; Wedin, David A. (Frontiers in Ecology and Evolution, 2019)
Heterogeneity has emerged as a fundamental principle for rangeland management and the importance of environmental heterogeneity for biological diversity has raised questions about the appropriateness of rangeland practices that seek to promote uniform grassland structure and composition. Principles of uniformity in rangeland management reflect a utilitarian target of “managing for the middle” by minimizing both overgrazing and underutilization while avoiding or preventing fire and other disturbances that consume aboveground biomass. We implemented a study to evaluate pioneering efforts to restore historical fire-grazer interactions via patch burning in an effort to increase spatial heterogeneity in the Nebraska Sandhills, a sandy soil, mixed-grass ecoregion with a long history of “management for the middle”. The application of patch burning did not increase landscape heterogeneity of vegetation structure or composition in the Nebraska Sandhills. Instead, grassland structure exhibited greater temporal variability than spatial variability in growing and dormant seasons. The low stocking rate and the rapid regrowth of live herbaceous vegetation following fire likely constrained the degree of spatial heterogeneity observed in our study and highlights the challenges of balancing forage supply and demand in semi-arid grasslands.